An enhanced CNN model for classifying skin cancer - Haider, Kazi MD Minhajul; Dhar, Mondira; Akter, Fahima; Islam, Sadia; Shariar, Syed Ragib (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022